2011
DOI: 10.1038/cgt.2011.52
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of subdural medulloblastomas using human neural stem cells expressing carboxylesterase

Abstract: The prognosis of medulloblastoma has improved significantly because of advances in multi-modal treatments; however, metastasis remains one of the prognostic factors for a poor outcome and is usually associated with tumor recurrence. We evaluated the migratory potential and therapeutic efficacy of genetically engineered human neural stem cells (NSCs) that encode a prodrug enzyme in the subdural medulloblastoma model. We genetically modified HB1.F3 (F3) immortalized human NSCs to express rabbit carboxylesterase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In turn, SN-38 preferentially kills dividing cancer cells specifically at the tumor sites [30]. We have previously reported that F3.CE cells migrate selectively to tumor sites and they have a therapeutic effect on disseminated neuroblastoma [26, 30], melanoma [28], ovarian cancer [19], breast cancer brain metastasis [17] and medulloblastoma [29] upon administration of prodrug CPT-11. Recently we also have reported that the NSCs expressing the cytosine deaminase (CD).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, SN-38 preferentially kills dividing cancer cells specifically at the tumor sites [30]. We have previously reported that F3.CE cells migrate selectively to tumor sites and they have a therapeutic effect on disseminated neuroblastoma [26, 30], melanoma [28], ovarian cancer [19], breast cancer brain metastasis [17] and medulloblastoma [29] upon administration of prodrug CPT-11. Recently we also have reported that the NSCs expressing the cytosine deaminase (CD).…”
Section: Discussionmentioning
confidence: 99%
“…F3.CE cells were used to treat various cancer cell types (subdural medulloblastomas, breast cancer, and lung cancer). These previous studies also reported the tropism of stem cells to cancer cells (16)(17)(18).…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, the establishment of an effective MB seeding model and the evaluation of the extent of tumor spread in live conditions are essential for studies on innovative therapeutics. For MB xenograft mouse models, four different injection routes have been introduced: intracerebral, subdural, intracerebellar, and intracisternal [4, 7, 9, 10]. Intracerebral and subdural (into the supratentorial subdural space) injections of MB cells have inherent limitations to identify MB characteristics in vivo because MB develops in or around the cerebellum and spreads via subarachnoid spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been described to establish the MB seeding model and involve transplanting human MB cells into the mouse cerebrum [7], cerebellum [8], subdural space [9], or cisterna magna [4, 10, 11]. However, each method possesses some limitations, such as the risks of surgical techniques, complexity of quantitative analysis in live animals, and difficulties of precisely simulating MB characteristics.…”
Section: Introductionmentioning
confidence: 99%